若y=3 √2x-3 +5 √(3-2x +6,求?(3次根号7)的xy次方若y=3 √(2x-3) +5 √(3-2x) +6,求(3次根号7)的xy次方根号下面的分别是 2x-3和3-2x

来源:学生作业帮助网 编辑:作业帮 时间:2021/06/14 22:20:30

若y=3 √2x-3 +5 √(3-2x +6,求?(3次根号7)的xy次方若y=3 √(2x-3) +5 √(3-2x) +6,求(3次根号7)的xy次方根号下面的分别是 2x-3和3-2x
若y=3 √2x-3 +5 √(3-2x +6,求?(3次根号7)的xy次方
若y=3 √(2x-3) +5 √(3-2x) +6,求(3次根号7)的xy次方
根号下面的分别是 2x-3和3-2x

若y=3 √2x-3 +5 √(3-2x +6,求?(3次根号7)的xy次方若y=3 √(2x-3) +5 √(3-2x) +6,求(3次根号7)的xy次方根号下面的分别是 2x-3和3-2x
因为2x-3≥0且3-2x≥0
所以x≥1.5且x≤1.5
x=1.5
代入y=3 √(2x-3) +5 √(3-2x) +6
y=0+0+6=6
xy=1.5*6=9
(3次根号7)的xy次方=?(3次根号7)的9次方=7^3=343

因为2x-3>=0且x>=0,所以x=3/2,所以y=6,xy=9
(3次根号7)的xy次方=7的3次方=343.
[根号里的数必须满足大于或等于0]